Quantum dot-layer-encapsulated and phenyl-functionalized silica spheres for highly luminous, colour rendering, and stable white light-emitting diodes - Yoo, Hyein; Jang, Ho Seong; Lee, Kwangyeol; Woo, Kyoungja (ROYAL SOC CHEMISTRY, 2015)
Although the quantum efficiencies of quantum dots (QDs) are approaching unity through advances in the synthesis of QD materials, their luminescence efficiencies after mixing with resin and thermal curing for white light-emitting diodes (LEDs) are seriously lowered because of aggregation and oxidation of QDs and poor adhesion of QDs to the resin. To overcome these problems, QD-layer-encapsulated and phenyl-functionalized silica (SQS(Ph)) spheres were synthesized and applied for white LEDs, whereby the QDs were homogeneously distributed at radial equidistance from the center and near the surface of approximately 100 nm-sized silica spheres and the surface was functionalized with phenylethyl groups. The inter-core distances of QDs were over similar to 14 nm, which is over the limit (<10 nm) for Forster resonance energy transfer (FRET) that leads to photoluminescence (PL) reduction. This hierarchical nanostructure excludes a chance of FRET between QDs and provides the QDs a gradually refractive index matching environment, which yields similar to 4-fold enhanced PL in SQS(Ph). More importantly, the SQS(Ph) acquired a highly adhesive property to silicone resin due to their phenyl functional group matching, which resulted in remarkably improved light extraction in white LEDs. When incorporated along with a yellow-emitting Y3Al5O12:Ce3+ (YAG:Ce) phosphor and silicone resin on blue LED chips, the SQS(Ph) spheres presented significantly improved performance [luminous efficiency (LE) = 58.2 lm W-1; colour rendering index Ra = 81.8; I/I-0 = 0.98 after 60 h operation] than their original QDs (LE = 39.6 lm W-1; Ra = 78.1; I/I-0 = 0.91 after 60 h operation) under a forward bias current of 60 mA.
Keywords: NANOCRYSTALS; CDSE; LUMINESCENT; EFFICIENT; PHOSPHORS